Cooperative hydrogen bonds form a pseudocycle stabilizing an isolated complex of isocyanic acid with urea. Issue 36 (7th September 2017) - Mullaney, John C.; Medcraft, Chris; Tew, David P.; Lewis-Borrell, Luke; Golding, Bernard T.; Walker, Nicholas R.; Legon, Anthony C.
Abstract : The structure and properties of a gas phase complex formed between urea and isocyanic acid are characterised through microwave spectroscopy and ab initio calculations at the CCSD(T)(F12*)/aug-cc-pVTZ level. Abstract : The shapes of macromolecules and their complexes with small molecules are often determined by extended networks of hydrogen bonds. Here, for the first time, we provide a detailed description of a cooperative pair of hydrogen bonds to an individual molecule of urea. The structure and properties of a gas phase complex formed between urea and isocyanic acid are characterised through microwave spectroscopy and ab initio calculations at the CCSD(T)(F12*)/aug-cc-pVTZ level.